Wheat thermoplastic starch composite films reinforced with nanocellulose - Jimat, Yusilawati Ahmad; Puad (Walter de Gruyter GmbH, 2023)
The rising costs of non-renewable plastic and environmental concerns with their industrial usage have encouraged the study and development of renewable products. As an alternative, biological-based materials create a huge opportunity for a healthy and safe environment by replacing non-renewable plastic in a variety of applications. Wheat is one of the worlds most widely cultivated crops. Due to its mechanical and physical properties, wheat starch is vital in the biopolymer industry. Wheat thermoplastic starch exhibits useable properties when plasticizers, elevated temperatures and shear are present. Thus, make it very suitable to be used as packaging material. However, this material suffers from low mechanical properties, which limit its applications. Several studies looked at the feasibility of using plant components which is nanocellulose as a reinforcing agent in wheat starch thermoplastic composites. Overall, the addition of nanocellulose can improve the performance of wheat thermoplastic starch, especially for its mechanical properties. It can potentially be used in several areas of packaging and biomedical. The objective of this review is to discuss several achievements regarding wheat starch/nanocellulose-based composites. Several important aspects of the mechanical performance and the thermal properties of the composites were evaluated. The discussion on wheat starch and nanocellulose was also tackled in this review